Traces of Presence: Pierre Soulages and the Status of Gesture in Postwar France. - Jimbo, Nolan M. (Tufts Archival Research Center, 2015)
In their unwavering monumentality, Pierre Soulages’s paintings conceal the gestural movements that created them, as the black painted forms sit so firmly and unshakably on the canvas that they seem to exist as integral parts of the surface rather than as results of human activity. In this way, Soulages’s paintings seem to exist solely as the traces of gesture, the memories of an act that can be alluded to but never fully recounted within the work. Taking this gap between trace and gesture as a premise, my thesis argues that Soulages’s paintings generate paradoxical impressions of presence and absence, as well as of embodiment and disembodiment, through their freezing of gesture into trace, and I illustrate this argument by placing Soulages’s paintings first in relation to the prehistoric cave paintings of Lascaux, France and subsequently with the drawings of French artist Henri Michaux.